Épségizmus elleni küzdelem a felsőoktatásban: feltáró kutatás az inklúzió folyamatelvű modellje mentén a Pécsi Tudományegyetem speciális szükségletű és neurodivergens hallgatóinak körében (2010–2022) és a partnerintézmények jógyakorlatainak tükrében - Tószegi J. Zsófia (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2024)
Jelen tanulmány a neurodiverzitást tárgyaló szakirodalom alapvetéseit foglalja össze, s a sokszínűségből mint értékből indul ki. Az épségizmust azzal a merész kijelentéssel vonja kérdőre, miszerint egy adott tanulóközösségben a speciális szükségletekkel élő vagy neurodivergens egyént nem is bármely testivagy érzékszervi fogyatékossága, pszichés fejlődési- vagy autizmus spektrum zavara korlátozza, hanem valójában az őt be nem fogadó, és a hozzá alkalmazkodni nem képes környezete teszi fogyatékossá (Ntombela-Mahlangu, 2019). A fogyatékosság szociális modellje a fogyatékkal élők társadalmi kirekesztettségének strukturális elemzését tette lehetővé (Hasler, 1993). Tudományos kutatások eredményei is alátámasztják a paradigmaváltást, miszerint a különféle gondolkodású, a máshogyan tanuló és a tananyaghoz másképp hozzáférő embertársaink patologizálása helyett a biodiverzitás elfogadására, az agyi változatok előnyeire, a részképességek fejleszthetőségére és a lehetőségek megteremtésére lenne hatékonyabb fókuszálni (Ranken, 2020). A tanulás és oktatási környezet egyetemes tervezésével (Universal Design of Learning) pedig az volna a cél, hogy egy-egy megoldás minél több hallgatónak, oktatónak és dolgozónak adjon lehetőséget a sikeres és hatékony részvételre (Bracken-Novak, 2019). De vajon a gyakorlatban mennyire követhető le ez a tudományos szemléletváltás? A fogyatékossággal élő hallgatók milyen tapasztalattal érkeznek hozzánk a PTE-re, s mit gondolnak az előnyben részesítésről? A befogadó környezet tovább tudott-e fejlődni az egyénileg kezelt problémák szintjéről egy intézményes stratégiaépítés felé? Mik a következő tennivalók a Támogató Szolgálat munkatársai és hallgatói szerint? Ezekre a kérdésre kerestem választ a PTE-n a sajátos nevelési igényük miatt sebezhető, ezért a felvételi pontszámításkor előnyben részesített hallgatókkal készült interjúim során. Bár a minta még nem reprezentatív, de mindenképp informatív abból a szempontból, hogy az Inklúzió Folyamatelvű Modellje (Varga, 2015) köré tematikusan csoportosíthatók az eddig felmerült kihívások és jógyakorlatok.

Abstract. My dissertation presentation will offer a literature review on the most recent findings of the current DEI research in the context of higher education students with disability, especially with a focus on neurodiversity. I have created a survey based on the original Booth-Ainscow Inclusion Index (UNESCO, 2015) in my translation into Hungarian. I have also created a Hungarian translation of the Inclusivity Tips for Educators with the permission of the expert consultant of the consortium and created a self-evaluation tool for faculty members based on the Inclusivity Tipp List for Educators (CHARMEU, 2021). The aims of these survey instruments are to explore the characteristics of inclusiveness in our higher education institutions. Among students who are underrepresented in HE, I focus specifically on a group with less visible disabilities, namely, neurodivergent individuals. Neurodiversity as an approach challenges ableism by boldly asserting, that in a learning community, individuals are not solely limited by their own physical, sensory or speech disabilities nor by their mental or cognitive developmental states, but they are in fact primarily disabled by their environment, which does not accept them or provide reasonable accommodations (Ntombela- Mahmangu, 2019). To what extent has this academic shift translated into practice? What are the experiences of students with disabilities (especially with neurodiversity) at our universities? Is “preferential treatment” enough to retain them, help them graduate and transition successfully to meaningful jobs? Has the inclusive environment been able to evolve from dealing with problems on an individual level to building an institutional strategy and collaborative system? What are the next steps for Support Service staff and students? I sought answers to these questions by started to analyze 10 years of student data collected by the Neptune Unified Education System, designed Surveys and semi-structured interview questions for students and faculty, and conducted individual and focus-group interviews with neurodivergent students (N=11), students with other disabilities (N=11) and Support Service staff (N=12) from the University of Pecs. My dissertation will also examine the inclusion policies and practices of three partner universities using document analyses, semi-structures interviews, participant observation and survey to highlight the successes and the challenges. Although the sample is not yet representative, it is certainly informative, and the qualitative data gained from the interviews and the open-ended survey questions (N=31) continue to give valuable insights to student experiences that can be thematically clustered around the pillars of the Process-based Model of Inclusion showing challenges that need to be tackled as well as best practices worth disseminating (Varga, 2015).
Challenging ableism in higher education: experiences of students with special needs & neurodiversity. Explorative research using a process-based model of inclusion at the University of Pecs (2010–2022) in light of the best practices from partner institutions
Keywords: inklúziós index; neurodiverzitás; fogyatékossággal élő hallgatók a felsőoktatásban